1982
DOI: 10.1172/jci110692
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound lactoferrin alters the surface properties of polymorphonuclear leukocytes.

Abstract: A B S T R A C T Polymorphonuclear leukocytes (PMN)aggregate and avidly attach to endothelium in response to chemotactic agents. This response may be related in part to the release of the specific granule constituent lactoferrin (LF). We found by using immunohistology and biochemical and biophysical techniques that LF binds to the membrane and alters the surface properties of the PMN. Upon exposure of PMN treated with 5 gg/ml cytochalasin B to 2 X 10' M formyl-methionine-leucine-phenylalanine for 5 min, the PMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 44 publications
4
32
0
1
Order By: Relevance
“…Lactoferrin receptors have been described previously for a variety of cells, including various leukocytes (34 -39) and epithelial cells (40). The binding affinities reported for the different cells vary widely, with the dissociation constants ranging from nanomolar to micromolar concentrations (34,35,(37)(38)(39)41). The results presented here for binding of 125 I-labeled lactoferrin by the eosinophils indicate that the affinity of the lactoferrin receptor on eosinophils also falls within this range.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Lactoferrin receptors have been described previously for a variety of cells, including various leukocytes (34 -39) and epithelial cells (40). The binding affinities reported for the different cells vary widely, with the dissociation constants ranging from nanomolar to micromolar concentrations (34,35,(37)(38)(39)41). The results presented here for binding of 125 I-labeled lactoferrin by the eosinophils indicate that the affinity of the lactoferrin receptor on eosinophils also falls within this range.…”
Section: Discussionsupporting
confidence: 52%
“…It is likely that the apparent two classes of lactoferrin receptors reflect at least in part the relative structural complexity of the 78-kDa lactoferrin molecule (24 -26). Of note, the apparent number of lactoferrin receptor molecules expressed by eosinophils is less than that reported for other cells (34,35,(37)(38)(39)41). Although complete saturation was not achieved in the binding experiments using 125 I-labeled lactoferrin, the results of the flow cytometric analysis indicate that binding of the lactoferrin by eosinophils is saturated following incubation with 30 g/ml (ϳ0.4 M) lactoferrin.…”
Section: Discussionmentioning
confidence: 62%
“…However, our results do not rule out that the DNA-binding protein whose expression is increased upon neutrophil activation is not a DNA receptor responsible for activation but a protein able to bind DNA and consequently cooperate in DNA binding to a transducing receptor. In fact, previous studies demonstrated that lactoferrin, a cationic protein contained in specific granules, is mobilized to plasma membrane upon neutrophil activation 48 and exhibits DNA-binding properties. 49 Moreover, we have also determined that myeloperoxidase and catepsin G, two cationic proteins contained in azurophilic granules, are able to bind DNA (JI Fuxman Bass, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Various reports indicate that LF may influence neutrophil recruitment to sites of infection by altering aggregation, adhesion, attachment, and/or motility of this cell type. [35][36][37][38] In addition, it has been shown that LF stimulates phagocytosis. 39,40 Finally, an enhancement of superoxide production by neutrophils was demonstrated in the presence of LF 37 whereas contradictory reports in neutrophils and cell-free systems support either an enhancement [41][42][43] or no effect 44,45 of LF on hydroxyl radical formation.…”
mentioning
confidence: 99%